Avaliação da segurança oncológica nas oncoplastias mamárias em comparação a cirurgia conservadora convencional - Silva, André Vallejo da (2008)
In recent years there has been a growing interest on enhancing the cosmetic and functional aspects of the oncological surgery of the breast, which resulted in the development of the oncoplastic surgery. This method presents several advantages, including the possibility of treating larger tumors with conservative procedures, better tumor-free margins, less carcinogenic risk in the future, better results with radiotherapy and finally, a better psychological profile of the patients. The most important factor regarding the oncological safety of the conservative surgery of the breast is the capacity of each procedure in providing tumor-free margins after resection. Therefore, we know that procedures that provide lager free margins are safer from the oncological point of view. In this study, we aimed to verify the oncological safety of the oncoplastic procedures in comparison with the traditional procedures, by comparing variables measured in two groups of patients surgically treated in the Breast Service of the HUAP. We could conclude that since the group operated with oncoplastic procedures had significant larger margins than the group operated with traditional techniques, and that the other variables measured were alike, it is possible to say that the oncological safety of the oncoplastic surgery of the breast is, at least, equal to the safety of the conservative surgery with traditional techniques.